The crash of 2008 and what it means : the new paradigm for financial markets - Soros, George; Soros, George (New York : PublicAffairs, 2009)
In the midst of one of the most serious financial upheavals since the Great Depression, George Soros, the legendary financier and philanthropist, writes about the origins of the crisis and proposes a set of policies that should be adopted to confront it. Soros, whose breadth of experience in financial markets is unrivaled, places the crisis in the context of his decades of study of how individuals and institutions handle the boom and bust cycles that now dominate global economic activity. In a concise essay that combines practical insight with philosophical depth, Soros makes an invaluable contribution to our understanding of the great credit crisis and its implications for our nation and the world.
Previous ed. published under title: The new paradigm for financial markets.
"Includes 4 new chapters"--Cover.
Includes bibliographical references and index.
rpm 15/05/13
Loans
Keywords: Financial crises; Credit; United States; United States